Problem-Based Learning in the Context of Mathematical Critical Thinking: A Bibliometric Trend Analysis - Shylvia, Putri Cinndy; Yulia, Cica; Sudiapermana, Elih; Sujana, Atep (Jurnal Pendidikan MIPA, 2025)
This study explores the integration of Problem-Based Learning (PBL) in mathematics education by mapping research trends on mathematical critical thinking through a bibliometric analysis of 791 Scopus-indexed publications from 2021 to April 2025. Employing a five-stage bibliometric protocol and VOSviewer software, the analysis visualizes keyword co-occurrence, research clusters, and networks among authors, institutions, and countries. The findings reveal a consistent increase in research interest, with a publication peak in 2024, reflecting the growing recognition of PBL as an effective approach to cultivating higher-order thinking skills. Indonesia emerged as the most productive country, with significant contributions from scholars such as Zubaidah S. and institutions like Universitas Negeri Malang and Universitas Negeri Surabaya. Dominant keywords include “problem-based learning” and “critical thinking”, which are strongly associated with other active learning strategies such as project-based learning, flipped classrooms, and collaborative learning. Importantly, the most influential articles predominantly originate from medical and nursing education, underscoring the interdisciplinary potential of PBL. This finding offers valuable insight for mathematics education researchers to adapt evidence-based approaches from other disciplines to strengthen theoretical and practical frameworks in their field. The study underscores the relevance of PBL in addressing 21st-century educational challenges and identifies potential research gaps in areas such as early mathematics education and qualitative approaches. The study not only highlights global engagement with PBL as a 21st-century learning model but also provides a roadmap for future investigations into unexplored areas such as early-grade mathematics education, qualitative methods, and digital PBL supported by artificial intelligence. By bridging pedagogical insights across disciplines, this research encourages more integrative, innovative, and impactful practices in advancing critical thinking through mathematics.  Keywords: problem-based learning, critical thinking, bibliometric analysis, mathematics education, VOSviewer.